(untitled) (Symposium on Natural and Applied Sciences, 2026)
This article examines the economic significance of vertically integrated value chains in the textile industry within the national economy, their role in enhancing production efficiency, and the specific features of fixed capital accounting in such systems. The study analyzes the impact of vertical integration on the investment climate, mechanisms for managing capital flows, and approaches to improving accounting systems. The research findings demonstrate that optimizing fixed capital accounting in vertically integrated textile enterprises contributes to improved financial stability and long-term competitiveness.